Marginal notes on the project for an etymological dictionary of the Mubi-Toram languages - Takács, Gábor (Lingua Posnaniensis, 2021)
The paper accompanies the second part of a planned longer series “Mubi-Toram lexicon and Afro-Asiatic” as a kind of belated extended introduction surveying some new results in the grouping of these languages as well as into some principles guiding our research designed to step by step reveal the Chadic and wider Afro-Asiatic cognate heritage in the lexical stock of the Mubi-Toram languages which represent the easternmost (26th) and sprachgeschichtlich perhaps the most enigmatic group of the vaste Chadic (i.e., 6th) branch of the gigantic Afro-Asiatic family.